Chest circumference and sitting height among children and adolescents from Lhasa, tibet compared to other high altitude populations. Issue 2 (7th August 2015) - Xi, Huanjiu; Chen, Zhao; Li, Wenhui; Wen, Youfeng; Zhang, Hailong; Xiao, Yanjie; Liu, Suwei; Pei, Linguo; Zhang, Meizhi; Lv, Po; Ren, Fu; Huang, Keqiang; et al.
Abstract : Objectives: The adaptation of human beings to a high altitude environment during growth has been reported in several populations but is less known for Tibetans. The objective of this study was to investigate similarities and differences of Tibetans in patterns and characteristics of physical growth and development in comparison to other high altitude populations. Methods: We measured the stature, weight, chest circumference and sitting height of 2, 813 healthy children and adolescents aged 6‐ to 21‐year‐old living at 3, 658–4, 500 m in Tibet, China, and compared them with published data from other high altitude populations. Eligible participants must have been born and raised in Tibet, and both their parents' families have to be Tibetan for at least the past three generations. Results: The physical growth and development of children and adolescents in Tibet and the Andes followed similar patterns, such as delayed growth, short stature and sitting height, and large chest dimensions. Relative to stature, Tibetan sitting heights are similar to Andeans, but chest circumferences are smaller. Conclusions: Findings from this study reinforce the conclusion that Tibetan and Andean populations have adapted differently to high altitude hypoxia. The physical features of each population may result from unique adaptation to hypoxia, as well as socio‐ecological factors, such as poor nutrition. Am. J. Hum. Biol. 28:197–202, 2016. © 2015 Wiley Periodicals, Inc.